Construção de marcador auxotrófico em Mycobacterium bovis BCG, de uma cepa knockout para DPPD e estudo proteômico da tuberculina - Borsuk, Sibele (2008)
Mycobacterium bovis BCG has the potential to be an effective live vector for multivalent vaccines. However, there are two problems regarding the utilization of recombinant BCG as vaccine. The first one is that most mycobacterial cloning vectors rely on antibiotic resistance gene as selectable marker, which is used for genetic transformation. The second one is the limited use of BCG in animals because it interferes in the tuberculosis diagnosis by tuberculin skin test, which elicits delayed type hypersensitivity to the purified protein derivative (PPD). In this work we developed and evaluated the use of auxotrophic complementation as a new selectable marker, characterized the proteins that are present in the bovine and avium PPD and developed a knockout BCG strain by homologous recombination. To test the auxotrophic complementation as selectable marker, an auxotrophic BCG strain for the amino acid leucine was constructed by knocking out the leuD gene by homologous recombination. Expression of leuD on a plasmid acted as a selectable marker in the auxotrophic M. bovis BCG leuD and M. smegmatis mc2144. The auxotrophic complementation selection was similar to selection by antibiotic resistance, but with the advantage of promoting stability of the plasmid. The new system was highly stable even during in vivo BCG growth. The identification of proteins from PPD was archived by LC-MS/MS (Liquid Chromatography/Mass Spectrometry/Mass Spectrometry). A total of 147 proteins among five PPD samples (2 bovine PPD and 3 avium PPD) were identified. The bovine PPD had a considerable higher number of proteins comparing to the avium PPD. We identifying a group of 28 proteins present only in bovine PPD and a group of five proteins deleted in M. bovis BCG vaccinal strain. These two groups are of special interest as they can be used in tests with improved specificity, and potentially able to differentiate vaccinated and infected individuals. A mutant BCG strain with the DPPD antigen deleted was constructed. The Mb0092 coding sequence was knocked out by homologous recombination. The 11 sequences flanking the target gene were cloned into a suicide vector. Double crossovers were selected using sacB. The knockout genotype was determined by PCR and by Southern blot. This mutant BCG strain can be useful in animal vaccination as it will not interfere in the tuberculosis diagnostic test, when performed using recombinant DPPD. The results show alternatives for the problems related to the use of M. bovis BCG as a recombinant vaccine. The auxotrophic complementation system was highly stable, efficient and it is suitable for expressing heterologous antigens in BCG. The identification of proteins present in PPD preparations and the mutant BCG obtained provide the possibility for the development of differential diagnostic test, thus allowing the use of BCG as vaccine also in animals.